Case Report: Unravelling the Mysterious Lichtenberg Figure Skin Response in a Patient With a High-Voltage Electrical Injury - Lindford, Andrew; Juteau, Susanna; Jaks, Viljar; Klaas, Mariliis; Lagus, Heli; Vuola, Jyrki; Kankuri, Esko (Frontiers in Medicine, 2021)
We describe a case of Lichtenberg Figures (LFs) following an electrical injury from a high-voltage switchgear in a 47 year-old electrician. LFs, also known as ferning pattern or keraunographic markings, are a pathognomonic skin sign for lightning strike injuries. Their true pathophysiology has remained a mystery and only once before described following an electical injury. The aim was to characterize the tissue response of LFs by performing untargeted non-labelled proteomics and immunohistochemistry on paraffin-embedded sections of skin biopsies taken from the area of LFs at presentation and at three months follow-up. Our results demonstrated an increase in dermal T-cells and greatly increased expression of the iron-binding glycoprotein lactoferrin by keratinocytes and lymphocytes. These changes in the LF-affected skin were associated with extravasation of red blood cells from dermal vessels. Our results provide an initial molecular and cellular insight into the tissue response associated with LFs.